القدرة التنبؤية للعوامل الكبرى للشخصية باليقظة العقلية: لدى طلبة جامعة اليرموك - صلاحات، محمد علي محمد; الزغول، رافع عقيل (جامعة القدس المفتوحة, 2018)
هدفت هذه الدراسة إلى معرفة القدرة التنبؤية للعوامل الكبرى للشخصية باليقظة العقلية، وهل يختلف مستوى اليقظة العقلية باختلاف الجنس أو التخصص لدى طلبة جامعة اليرموك. تكونت عينة الدراسة من (760) طالباً، وطالبة من طلبة مرحلة البكالوريوس في جامعة اليرموك. وجرى استخدام مقياس الوجوه الخمسة لليقظة العقلية(Baer et al., 2006) ، ومقياس العوامل الكبرى للشخصية، الذي طور من مقياس العوامل الخمسة الكبرى للشخصية لكوستا وماكري (Costa & McCrae, 1992)، بعد التحقق من مؤشرات الصدق والثبات. وأظهرت نتائج الدراسة أن مستوى اليقظة العقلية لدى الطلبة كان متوسطاً على الأداة ككل وفي الأبعاد باستثناء بعد المراقبة كان مرتفعاً، كما كشفت نتائج الدراسة وجود فرق ذي دلالة إحصائية يعزى لمتغير الجنس في بعد المراقبة لصالح الإناث، ووجود فروق ذات دلالة إحصائية تعزى لمتغير الكلية في جميع الأبعاد باستثناء بعد الوصف، لصالح الكليات الإنسانية في بعدي: العمل بوعي، وعدم الحكم على الخبرة الداخلية، ولصالح الكليات العلمية في بعدي: المراقبة، وعدم التفاعل مع الخبرة الداخلية، وأخيراً أظهرت النتائج أن هنالك أربعة عوامل ساهمت في تفسير (25.4%) من اليقظة العقلية وهي: العصابية (17.7%)، ويقظة الضمير (6.1%)، والاعتدال (0.8%)، والانبساطية (0.8%).
This study investigated the predictive ability of big personality factors towards mindfulness, and whether the level of mindfulness varies according to students’gender or academic specialization among Yarmouk University Students. The sample of the study consisted of (760) male and female students at Yarmouk university. The study adopted Baer's five facet mindfulness scale, and Costa & McCrae's scale. The results showed that the level of mindfulness among students was moderate in general and in all facets except in the facet of observing, which came high. Furthermore, the results showed significant differences in observing facet due to gender in favor of females. Moreover, the results showed significant differences in all facets of mindfulness due to the variable of faculty except in the facet of describing, in favor of human sciences majors in the two facet, acting with awareness and non- judging. There were difference in favor of the scientific majors in the facets of observing and non- reactivity to inner experience. Finally, the results showed that four factors contributed in the explanation of (25. 4%) of mindfulness. These factors are, Neuroticism (17. 7%), Conscientiousness (6. 1%), moderation (0. 8%), Extraversion (0. 8%).
Keywords: السمات الشخصية -- اليقظة العقلية -- طلاب الجامعات -- علم النفس التربوى -- جامعة اليرموك